Managing the unmanageable: Deviation in project success within the project life cycle in the Icelandic construction industry - Svanborg María Guðmundsdóttir 1992- (2021)
Globally, the construction industry has a significantly low score regarding the number of projects which attain their stated aims. Research shows that construction projects most often overrun. Construction projects can be very complex, and many layers need to synergize for them to be successful. The construction industry in Iceland is no exception, and many construction projects are not completed according to schedule. It is extremely costly when projects do not achieve their goals. Previous research shows there are various reasons for this kind of deviation to occur in the construction industry. Examples include poor project management and/or organization, lack of scope, poor use of labor, clients whose budgets are insufficient, interference from the client, and also uncontrollable factors such as the weather. The influence of the newest obstacle, COVID19, is extremely unpredictable. The purpose of this research was to investigate the Icelandic construction industry to enquire and establish exactly where deviation occurs within project management, why it does so, and how such deviations manifested during the project life cycle. To perform this research, a qualitative research method was used. Eight semi-structured interviews were conducted with experienced engineers, who have either been project managers or part of a project management team. Based on these interviews, the research indicates that deviation in projects mostly occurs due to four factors. Firstly, when the client is too indefinite about their requirements. When the client is indefinite, it leads to an undervaluation of the project’s actual scope in the deviation phase; the resulting lack of planning then creates an extended executions phase, often with greatly increased costs. Secondly, attitudes that are quite prevalent in Icelandic culture, an aspect that was not unknown to previous researchers, appear to impact detrimentally on the project outcome. This specifically relates to how comfortably people can live with uncertainty whilst maintaining ...